2019
DOI: 10.2196/14529
|View full text |Cite
|
Sign up to set email alerts
|

Predictors Linking Obesity and the Gut Microbiome (the PROMISE Study): Protocol and Recruitment Strategy for a Cross-Sectional Study on Pathways That Affect the Gut Microbiome and Its Impact on Obesity

Abstract: Background The prevalence of obesity has increased substantially over recent decades and is associated with considerable health inequalities. Although the causes of obesity are complex, key drivers include overconsumption of highly palatable, energy-dense, and nutrient-poor foods, which have a profound impact on the composition and function of the gut microbiome. Alterations to the microbiome may play a critical role in obesity by affecting energy extraction from food and subsequent energy metaboli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 65 publications
0
12
0
1
Order By: Relevance
“…We have mentioned social media in the context of informing and reminding, and this technology has been highlighted as a modern way of recruiting subjects to trials. Knowledge of special interest groups on these media may find subjects that are difficult to recruit through ordinary channels (worksite or clinic), 21 23 but concerns have also been raised regarding representativeness of samples and protection of subjects. 24 Also, a study explored Facebook to recruit males into health service research, but concluded that a multi-faceted approach was needed.…”
Section: Discussion/consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have mentioned social media in the context of informing and reminding, and this technology has been highlighted as a modern way of recruiting subjects to trials. Knowledge of special interest groups on these media may find subjects that are difficult to recruit through ordinary channels (worksite or clinic), 21 23 but concerns have also been raised regarding representativeness of samples and protection of subjects. 24 Also, a study explored Facebook to recruit males into health service research, but concluded that a multi-faceted approach was needed.…”
Section: Discussion/consequencesmentioning
confidence: 99%
“…In order to judge the quality of an intervention study, we encourage transparent reporting of the recruitment procedure, as this reflects directly on the generalisability of the results. We have found one example of specifying the recruitment strategy in the trial protocol, 21 which also is a good idea for increased transparency. It is important to know if the included sample was indeed representative of the source population (a point in many quality checklists 28 29 ).…”
Section: Discussion/consequencesmentioning
confidence: 99%
“…Environmental pollutants affect the fish's health by influencing various metabolic pathways, especially on the food intake and the subsequent energy transformation, and finally induce host obesity [61,62]. Thus, the alteration of gut microbiota exposed to environmental challenges is always related to the diseases in the host or the metabolic functions [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Human beings exist in a mutualistic relationship with their gut microbiota, a highly diverse and complex microbial ecosystem closely associated with various phenotypes and diseases [11,12]. Perturbations in gut microbe richness and diversity affect the levels of 5-HT, norepinephrine, and γ-aminobutyric acid (GABA)ergic and dopaminergic neurotransmission in the brain [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Widespread access to online tools now offers various advantages in data collection that can reduce administrative procedures and improve information privacy [17,18]. Previous studies have demonstrated that performance and effectiveness obtained using online recruitment methods in studies of sexual issues or gut microbes concur with those obtained using offline recruitment methods, such as telephone surveys, mail-in questionnaires, posters, and flyers [12,[19][20][21]. In addition, online surveys may even provide greater reach and be less expensive, while allowing for convenient data collection and analysis [22][23][24].…”
Section: Introductionmentioning
confidence: 99%